New Endovascular Approach for Hypothermia With Intrajugular Cooling and Neuroprotective Effect in Ischemic Stroke. Issue 2 (February 2020) - Duan, Yunxia; Wu, Di; Huber, Mitchell; Shi, Jingfei; An, Hong; Wei, Wenjing; He, Xiaoduo; Ding, Yuchuan; Ji, Xunming
Abstract : Background and Purpose—: Induction of hypothermia as a stroke therapy has been limited by logistical challenges. This study was designed to determine the hypothermic and neuroprotective efficacy of infusing cold saline directly into the internal jugular (IJ) vein and compare the effects of IJ hypothermia to those achieved by intracarotid artery hypothermia in an ischemic stroke model. Methods—: The right middle cerebral artery was occluded in rats using an intraluminal filament. Immediately following reperfusion, hypothermia was achieved by infusing isotonic saline through microcatheter into the right IJ or right intracarotid over 30 minutes. Infarct sizes, neurological deficits, blood-brain barrier damage, edema volume, blood-brain barrier associated molecules (MMP-9 [matrix metallopeptidase 9] and AQP-4 [aquaporin 4]), and apoptosis-associated proteins (Bcl-2 and cleaved Caspase-3) were measured. Results—: We found that both IJ- and intracarotid-based infusion cooled the brain robustly with a minimal effect on rectal temperatures. This brain cooling led to significantly reduced infarct volumes at 24 hours after reperfusion, as well as decreased expression of the proapoptotic protein cleaved Caspase-3 and increased expression of the antiapoptotic protein Bcl-2. Intracarotid and IJ cooling also aided in blood-brain barrier maintenance, as shown by decreased edema volumes, reduced Evans Blue leakage, and decreased expression of edema-facilitating proteins (MMP-9 and AQP-4). Both cooling methods then translated to preserved neurological function as determined by multiple functional tests over a 28-day observation period. Most importantly, the cooling and neuroprotective efficacy of IJ cooling was comparable to intracarotid cooling by almost every metric evaluated. Conclusions—: Compared with intracarotid infusion, IJ infusion conferred a similar degree of hypothermia and neuroprotection following ischemic stroke. Given the ease of establishing vascular access via the internal jugular vein and the powerful neuroprotection that hypothermia provides, IJ brain cooling could be used as a promising hypothermia-induction modality going forward. Abstract : Supplemental Digital Content is available in the text.